A cell-based sensor deployment strategy with improved coverage for mobility-assisted hybrid wireless sensor networks. (19th March 2010) - Sung, Tien-Wen; Yang, Chu-Sing
The deployment of wireless sensor devices is one of the most fundamental and important issues in wireless sensor network applications, and coverage is a chief consideration in deployment requirements. This paper proposes a hexagonal cell-based sensor deployment strategy that adopts a mobility-assisted hybrid wireless sensor network. Calculation of coverage hole size, the corresponding hole-healing process and discovery of nearly redundant sensors are based on the hexagonal cells into which the sensing field is virtually divided. Simulations show that the proposed algorithm achieves significantly improved field coverage, and indicates both the number and the influence of nearly redundant sensors in the wireless sensor network.